MEMBANGUN CITRA BUDAYA MASYARAKAT SUMENEP MELALUI FESTIVAL MUSIK TONG-TONG - Mohammad Insan Romadhan (Metacommunication: Journal of Communication Studies, 2020)
Sumenep is the easternmost region of the island of Madura which has a lot of potential for both natural and cultural tourism. But behind this great potential, there is one problem that needs to be considered, namely the community's stigma of the culture of the Madurese community itself. In general, the culture of Madurese people is known as a hard, firm and tend to be rough society. Even though Madurese culture is not what people generally think. It is the duty of the regional government to be able to rebuild the self-image of the Madurese community, especially Sumenep. Based on this the researcher is interested in studying the effort to build the cultural image of the Sumenep community through the tong-tong music festival. The theoretical study in this study uses the impression management theory to see the phenomenon of the use of music tongs in building the cultural image of the Sumenep community, while the Laswell communication model is used to see the use of this festival as a medium for delivering messages. This research approach uses qualitative descriptive research. The informant of this study was the head of promotion of the Department of Tourism, Youth Culture and Sports. Data collection uses interviews, observation, and documentation. The results showed that in building the cultural image of the people of Sumenep, they tended to use the ingratiation strategy (pleasing others) and the self-promotion strategy. Both of these strategies are widely applied by showing the characteristics possessed by Sumenep by using attributes that indeed show the culture of the Sumenep community. In addition, the way that is carried out through the tong music festival also contains elements of entertainment that can provide fun to others.